Comparing the effectiveness of Cinnamomum zeylanicum essential oil and two common household sanitizers to reduce lettuce microbiota and prevent Salmonella enterica recontamination. Issue 2 (27th January 2022) - Rossi, Chiara; Maggio, Francesca; Casaccia, Manila; Chaves‐López, Clemencia; Valbonetti, Luca; Serio, Annalisa; Paparella, Antonello
Abstract: The washing step is necessary to remove biological and physical hazards from minimally processed vegetables. Nevertheless, the risk of foodborne diseases could persist even after washing due to postsanitizing contamination, and little is known about the antimicrobial effect of residual sanitizers. This study was conducted to compare the effectiveness of sodium hypochlorite (SH), sodium bicarbonate, and Cinnamomum zeylanicum essential oil (CEO) as sanitizers on lettuce (8°C, 48 h). First, the effect of sanitizers in reducing total aerobic mesophilic and psychrotrophic bacteria, yeast and molds, lactic acid bacteria, and Enterobacteriaceae on lettuce was evaluated with some insights on lettuce quality attributes (pH, color, and sensory analysis). Then, the capability of the treatments in preventing postwashing Salmonella adhesion on lettuce surface was investigated. Commercial SH disinfectant (solution at 2%) and CEO (0.5%) reduced microbial contamination in lettuce, without affecting the overall acceptability after 48 h at 8°C. SH reduced postsanitizing Salmonella adhesion of about 2.7 Log colony forming unit (CFU)/g. The microbial reduction was confirmed by confocal laser scanning microscopy, which also evidenced Salmonella internalization within stomata. Interestingly, CEO as well reduced Salmonella adhesion but with lower efficacy (0.44–1.00 Log CFU/g reduction), while sodium bicarbonate (15 mg/ml) was not effective. In conclusion, SH and CEO seem to be effective sanitizing agents, capable of improving the microbiological profile of fresh produce. In addition, the residual sanitizers, that remain on lettuce after washing, play a role in reducing Salmonella adhesion. Abstract : Chlorine‐based sanitizer (SH) and CEO decrease lettuce microbiota. SH and CEO reduce post‐sanitizing Salmonella adhesion. Sodium bicarbonate is not effective in microbial count reduction.